Legal Politics and Norm Contestation in the New Criminal Code in the Framework of Indonesian Criminal Law Reform - Raymundus Loin; Marlina Samosir; Edmundo Octovianus Loin (Program Studi Hukum Diluar Kampus Utama Universitas Pattimura Kabupaten Maluku Barat Daya, 2026)
The formation of the New Criminal Code marks a crucial phase in the journey of Indonesian criminal law reform. As a product of legal politics born of a long process, the New Criminal Code not only brings substantial reforms but also gives rise to various normative contestations that influence the consistency and direction of the national criminal law system. This study aims to determine the legal politics of the formation of the New Criminal Code reflecting the direction of Indonesian criminal law reform and the legal politics and normative contestations within the New Criminal Code within the framework of Indonesian criminal law reform. This study uses normative juridical legal research, where the data is sourced from secondary data. The results show that the legal politics of the formation of the New Criminal Code reflect the state's commitment to renewing the national criminal law system by abandoning the colonial paradigm and emphasizing the values ​​of Pancasila. This reform indicates a direction for Indonesian criminal law that is more modern, proportional, and responsive to the needs of society. The legal politics and normative contestations within the New Criminal Code indicate a direction for Indonesian criminal law reform that emphasizes the independence of national legislation, but still leaves behind the dynamics of differing values ​​and interests. This indicates the need for further harmonization to ensure a more consistent criminal law system and in line with societal developments.